2020
DOI: 10.1093/jrr/rraa116
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on wild medaka around Fukushima Dai-ichi Nuclear Power Plant assessed by micronucleus assay

Abstract: Since the Fukushima Dai-ichi Nuclear Power Plant (F1-NPP) accident in 2011, radiation effects on wildlife in the contaminated areas have been a major concern. The outskirts of the F1-NPP are mainly rural areas, where many rice fields, streams and reservoirs are located. We searched for wild medaka (small aquarium fish) around the F1-NPP and found two wild medaka habitats (S1 and S2). S1 is a stream located 4 km from the F1-NPP, where the ambient dose equivalent rate was 0.4–0.9 μSv/h (2013–14), and S2 is a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The radiation impacts on wildlife in the FDNPP-contaminated areas have been studied in animals, insects, and plants, and present data showed either significant or non-significant radiation effects [29,36]. Radiation exposure also affects reproductive functions, particularly in the testis, as it is one of the most radiosensitive organs [37]. Here, we investigated the testicular ultrastructure of A. speciosus, albeit on a low number of samples, aiming to gain insights into the potential reproductive impacts associated with various radiation exposure dose rates caused by the release of radioactive material from the FDNPP accident.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The radiation impacts on wildlife in the FDNPP-contaminated areas have been studied in animals, insects, and plants, and present data showed either significant or non-significant radiation effects [29,36]. Radiation exposure also affects reproductive functions, particularly in the testis, as it is one of the most radiosensitive organs [37]. Here, we investigated the testicular ultrastructure of A. speciosus, albeit on a low number of samples, aiming to gain insights into the potential reproductive impacts associated with various radiation exposure dose rates caused by the release of radioactive material from the FDNPP accident.…”
Section: Discussionmentioning
confidence: 60%
“…During the seasonal reproductive cycle, the regulation of spermatogenesis is controlled by proliferation and apoptosis in male germ cells, including spermatogonia and primary spermatocytes [12,21]. Furthermore, previous studies reported differences in radiation sensitivity between spermatogonia and spermatocytes [38], even among the various stages of the spermatogenic cycle [37,39,40]. As spermatogenesis serves as an indicator of ecological factors influencing animal reproduction, it holds significance in the context of studying radiation effects on reproductive systems.…”
Section: Discussionmentioning
confidence: 99%
“…After the accident of the Chernobyl nuclear power plant in 1986, researchers recognized the need to closely examine the impacts of low dose and low dose-rate irradiation on living organisms and ecosystems, and numerous studies have been started and are still ongoing (International Atomic Energy Agency [IAEA], 2006;Braga-Tanaka et al, 2018;Kamstra et al, 2018). In 2011, the Fukushima Daiichi nuclear power plant caused the accident to contaminate the wide area of east Japan (International Atomic Energy Agency [IAEA], 2015; Johansen et al, 2015;Maruyama et al, 2021). It has made the researchers to recognize again the need to elucidate the impacts of low dose and low dose-rate irradiation and has accelerated the research, especially in Japan (Hiyama et al, 2012;Braga-Tanaka et al, 2018;Shimura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%